Persepsi Atlet Tarung Derajat (Satlat Masbagek) Terhadap Pemanfaatan Sport Massage Sebelum Bertanding - Jamaludin, Jamaludin; Wijaya Kusuma, Lalu Safta (JUPE : Jurnal Pendidikan Mandala, 2024)
There is a lack of understanding and knowledge among fighting athletes regarding the benefits of sports massage before competing. The problem in this research is the perception of masbagek satlat fighting athletes regarding the use of sports massage before competing. The aim of this research was to determine the perceptions of Masbagek combat athletes regarding the use of sports massage before competing. The population in this study were advanced fighting athletes who actively trained at the Masbagek satlat, totaling 18 athletes. Sampling used a population method consisting of 18 athletes. The survey research method uses a questionnaire, while data analysis uses a percentage descriptive statistical analysis formula. The results of this research show that 22.2% of respondents achieved the very useful criteria because respondents used sports massage by understanding the physical and psychological effects before competing so that respondents assumed that using sports massage before competing was a need that must be met. Likewise, 22.2% of respondents thought that sports massage was useful before competing, even though respondents knew of its positive physical and psychological effects. And as many as 55.5% of respondents said that sports massage was not useful because the respondents did not really know about sports massage so that sports massage was sometimes done, sometimes not, and even if it was done, it was not ordered by someone who was competent in sports massage or used traditional massage. . So, the use of sports massage before competing for high-level combat athletes is highly recommended.